Agronomic performance of white maize landrace in different environmental conditions - Ana Raquel Ribeiro e Souza (Revista Ceres, 2008)
The aim of this study was to evaluate the agronomic performance of the white maize landrace rescued in Barbacena, MG, Brazil in its home country, in southeast Minas Gerais and northern Rio de Janeiro at the altitude of 1,100 m, 650 m and 14 m above sea level, respectively. In Barbacena, the climate is temperate with dry winters (Cwb) and the soil type is a dystrophic red Oxisol. In southeast Minas Gerais, the climate is humid tropical (Cwa) and the soil is a dystrophic red-yellow Argisol stage terrace. In northern Rio de Janeiro, the climate is maritime tropical and the soil is a dystrophic yellow Oxisol. The white maize landrace was selected by farmers in Barbacena for several decades and has no agronomic information. Three experiments were set up with 100 half-sib progeny in the Campos dos Goytacazes, RJ, in Coimbra, MG and in Barbacena, MG. Analysis of variance found significant differences between the progeny average of all characters evaluated in the three environmental conditions. Plant height (PH, 2.39 m – 2.95 m), ear height (EH, 1.49 – 1.95 m) and EH/PH (63% – 69%) were deemed unfit for the production system with high plant density. The average grain yield was 820 kg ha Barbacena. Yields were considered low in relation to the lack of population response to inputs such as fertilizer and irrigation, plant density and lack of adaptation to the environmental conditions found in Campos dos Goytacazes and Coimbra. It was concluded that the farmers have a production system that is well adapted to local conditions, but with limited grain yield; it is necessary to carry out pre-breeding selection in the population before using it directly.